Applying Innovative Trends in the Process of Higher Education Security Personnel in Order to Increase Efficiency. (13th May 2015) - Kováčová, Lucia; Vacková, Martina
Abstract: Article deals with the security education in the conditions of universities, the implementation of innovative trends into this process due to increasing its effectivity. When solving the problems in the area of security, the important aspect is education and professional training of the employees of security services, but also workers and managers at different levels in the area of security, where high knowledge demands are required. In the context of education at universities, security awareness of people coming from schools to work may help to increase better conditions in this area. Deepening their knowledge and skills connected with the security, increasing qualification and training of graduates, preparation for solving crisis and emergency phenomena in different areas of security (civil, economic, environmental, technical and technological, logistical, and etc.) may also help to increase better conditions in this area. If we use security education as intensive factors of economic, social growth of the companies to, it is important to know how such methods, forms and means in which the intensity and under what circumstances it is necessary to work on learning to achieve effectiveness of the resulting learning.